A proteção dos dados pessoais e tutela da vulnerabilidade do consumidor frente à tecnologia da mineração de dados. - Vasconcelos, Sthéfane Alves (2022)
Law is conditioned by the realities of the environment in which it manifests itself, and contemporaneity has brought new challenges, as issues that were not even a legal concern, began to require analysis and regulation. New interests and legal situations, both patrimonial and existential, arise through the advancement of technology, being necessary to adopt new paradigms in order to reconcile the speed of technological evolution with the legal protection of the fundamental rights of the individual, especially the consumer, part admittedly vulnerable in the consumption relationship. The socalled Data Mining is one of the main technologies present in practically all computing applications used by society, and is part of a series of advances that are in line with the beginning of an era of transforming data into information. Consumer’s vulnerability is not a new topic, already being addressed in the Consumer Defense Code, however, given the contours of contemporary society, marked by the fluidity of relationships and consequent fragility of legal certainty, there is a new bias of consumer’s vulnerability in the digital field, which can even harm their free personality development. To fulfill the objective of this research, adopting the deductive method, a theoretical-based investigation was carried out, with compilation and bibliographic review on the exposed themes, focusing on the analysis of national and foreign texts and also of normative documents, such as the Federal Constitution of 1988, the Consumer Defense Code, and the General Data Protection Law. Seeks to verify the effectiveness of a constitutional protection, reinforced by the LGPD, to give consumers the opportunity to preserve their fundamental rights and the free development of their personality, in order to enable their empowerment in this technological environment. And, through a reinterpretation of civil liability, with the adoption of the theory of the dialogue of the sources, it is exposed about the possibility of the formation of a fundamental protection norm, concluding on the need for new postures and legal positions in order to ensure a consistent level of consumer protection, so that there is harmony and balance with technological development.